Pengembangan Kesenian Tradisional Joget Dangkong di Sanggar Sang Nila Utama Kecamatan Bintan Utara Kabupaten Bintan Provinsi Kepulauan Riau - Balqista Andriani Putri; Darmawati Darmawati (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research aims to find out and discuss the development of Dangkong Dance in Sanggar Sang Nila Utama, North Bintan District, Bintan Regency. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the development process of Joget Dangkong carried out by the researcher with Sutarto as the head of the studio is to increase the number of actors taken from the younger generation in North Bintan District, Bintan Regency. The development carried out at the Sang Nila Utama Studio consisted of six meetings, where previously the perpetrators only numbered 5-8 people and after the training of the Dangkong Dance perpetrators increased to 20 perpetrators. Dangkong Dance is displayed at school farewell events, entertainment events and enlivens events at Club Med Bintan in Lagoi so that Dangkong Dance continues to exist and develop to the next generation.